Scanning capacitance microscopy registration of buried atomic-precision donor devices. (3rd February 2015) - Bussmann, E; Rudolph, M; Subramania, G S; Misra, S; Carr, S M; Langlois, E; Dominguez, J; Pluym, T; Lilly, M P; Carroll, M S
Abstract: We show that a scanning capacitance microscope (SCM) can image buried delta-doped donor nanostructures fabricated in Si via a recently developed atomic-precision scanning tunneling microscopy (STM) lithography technique. A critical challenge in completing atomic-precision nanoelectronic devices is to accurately align mesoscopic metal contacts to the STM defined nanostructures. Utilizing the SCMs ability to image buried dopant nanostructures, we have developed a technique by which we are able to position metal electrodes on the surface to form contacts to underlying STM fabricated donor nanostructures with a measured accuracy of 300 nm. Low temperature ( T = 4 K) transport measurements confirm successful placement of the contacts to the donor nanostructures.